P53 dysregulation in B-cell malignancies: More than a single gene in the pathway to hell. Issue 4 (July 2017) - Tessoulin, B; Eveillard, M; Lok, A; Chiron, D; Moreau, P; Amiot, M; Moreau-Aubry, A; Le Gouill, S; Pellat-Deceunynck, C
Abstract: TP53 deletion or mutation is frequent in B-cell malignancies and is associated with a low response rate. We describe here the p53 landscape in B-cell malignancies, from B-Acute Lymphoblastic Leukemia to Plasma Cell Leukemia, by analyzing incidence of gain or loss of function of actors both upstream and within the p53 pathway, namely MYC, RAS, ARF, MDM2, ATM and TP53 . Abnormalities are not equally distributed and their incidence is highly variable among malignancies. Deletion and mutation, usually associated, of ATM or TP53 are frequent in Diffuse Large B-Cell Lymphoma and Mantle Cell Lymphoma. MYC gain, absent in post-GC malignancies, is frequent in B-Prolymphocytic-Leukemia, Multiple Myeloma and Plasma Cell Leukemias. RAS mutations are rare except in MM and PCL. Multiple Factorial Analysis notes that MYC deregulation is closely related to TP53 status. Moreover, MYC gain, TP53 deletion and RAS mutations are inversely correlated with survival. Based on this landscape, we further propose targeted therapeutic approaches for the different B-cell malignancies.